Low-redshift quasars in the SDSS Stripe 82: associated companion galaxies and signature of star formation - Bettoni D; Falomo R; Kotilainen JK; Karhunen K (OXFORD UNIV PRESS, 2022)
We obtained optical spectroscopy of close (< 80 kpc) companion objects of a sample of 12 lowredshift quasars (z < 0.3) selected from the SDSS Stripe82 area and that are in the subsample of 52 QSOs for which both multicolour host galaxies properties and galaxy environment were recently investigated in detail. We found that for 8 out of 12 sources the companion galaxy is associated with the QSO having a difference of radial velocity that is less than 400 km s(-1). Many of these associated companions exhibit [OII] lambda 3727 angstrom emission lines suggestive of episodes of (recent) star formation possibly induced by past interactions. The star formation rate of the companion galaxies as derived from [OII] line luminosity is, however, modest, with a median value of 1.0 +/- 0.8 M-circle dot yr(-1), and the emission lines are barely consistent with expectation from gas ionization by the QSO. The role of the QSO for inducing star formation in close companion galaxies appears meager. For three objects we also detect the starlight spectrum of the QSO host galaxy, which is characterized by absorption lines of old stellar population and [ O II] emission line.